New manufacturing techniques for antennas - Nash, Michael (My University, 2009)
This paper is a discussion of new manufacturing techniques for antennas. Many existing manufacturing methods, including conductive ink printing, plastic plating, hot foil printing, etching, sintering and die cutting, are investigated to determine their usefulness in the manufacture of antennas. The advantages and disadvantages of each are discussed, and the most promising method—plating on plastic—is further analysed. The method of adapting the plating technique so that it can be used for antennas is discussed. Two prototype antennas (a PIFA and omni antenna) were manufactured to test the plating method’s effectiveness as a manufacturing technique for antennas. Results showed a frequency shifted VSWR pattern for the PIFA antenna of 10% on each notch. The gain plot for the omni antenna showed a higher gain for the plated antenna at a frequency shifted by approximately 0.4 GHz. A cost analysis was also performed to complete the investigation of the new manufacturing method. A saving of up to 4 000% can be realised on the substrate material, and the metal costs can be lowered by 700% for each PIFA antenna.